|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 16:45:08
|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值
|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值
|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值
|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值|ab-2|+(b-1)的平方=0,求 1/ab +1/(a+1)(b+1) +1/a+2)(b+2)+ .+1/(a+ 2010)(b+2010)的值
|ab-2| (b-1)的平方=0 ab-2=0,b=1 a=2,b=1 1/ab 1/(a b)(b 1) 1/(a 2)(2 b) ```````` 1/(a 2008)(b 2008) =1/1*2 1/2*3 1/3*4 1/2008*2009 =(1-1/2) (1/2-1/3) (1/3-1/4) . (1/2008-1/2009) =1-1/20
等于2009
2
According to ab=2 & b=1, a=2
(1-1/2)+(1/2-1/3)+(1/3-1/4)+……+(1/2011-1/2012)=1-1/2012=2011/2012